1998
DOI: 10.1002/(sici)1096-9837(199806)23:6<561::aid-esp870>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability of floodplain sedimentation at the event scale in the Rhine–Meuse delta, The Netherlands

Abstract: This article addresses spatial variability of comtemporary floodplain sedimentation at the event scale. Measurements of overbank deposition were carried out using sediment traps on 11 floodplain sections along the rivers Waal and Meuse in The Netherlands during the high-magnitude flood of December 1993. During the flood, sand sheets were locally deposited behind a natural levee. At distances greater than 50 to 100 m from the river channel the deposits consisted mainly of silt-and clay-sized material. Observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
3
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 14 publications
2
83
3
1
Order By: Relevance
“…Floodplain deposition can lead to considerable trapping of sediment and POM amounting to 10-40 % of the annual load (e.g., Walling et al, 2003). Current estimates are based on measured conveyance losses (e.g., Lambert and Walling, 1987), deposition measured during post-event surveys (e.g., Middelkoop and Asselman, 1998;Steiger et al, 2003), and modeling studies (Hung, 2011;Middelkoop and Van der Perk, 1998;Nicholas and Walling, 1997). Sediment trapping efficiencies in floodplains depend on -apart from sediment settling rates -water discharge over the floodplain, the inundated floodplain area and depth, and residence time of the flood water.…”
Section: Floodplain Sediment and Poc Depositionmentioning
confidence: 99%
“…Floodplain deposition can lead to considerable trapping of sediment and POM amounting to 10-40 % of the annual load (e.g., Walling et al, 2003). Current estimates are based on measured conveyance losses (e.g., Lambert and Walling, 1987), deposition measured during post-event surveys (e.g., Middelkoop and Asselman, 1998;Steiger et al, 2003), and modeling studies (Hung, 2011;Middelkoop and Van der Perk, 1998;Nicholas and Walling, 1997). Sediment trapping efficiencies in floodplains depend on -apart from sediment settling rates -water discharge over the floodplain, the inundated floodplain area and depth, and residence time of the flood water.…”
Section: Floodplain Sediment and Poc Depositionmentioning
confidence: 99%
“…The inverse relationship between elevation and sedimentation rate (Walling et al, 1996;Walling and He, 1998) could not be confirmed by this study. As Middelkoop and Asselman (1998) and Thonon et al (2007b) found, this might be attributed to levees and other topographic features. Moreover, high flow velocities at low-lying areas can even reverse this trend at certain flood magnitudes (Asselman and Middlekoop, 1998).…”
Section: Linear Mixed-effect Modelsmentioning
confidence: 99%
“…At this scale, previous studies have indicated that distance from the main channel exerts more influence on spatial variability of overbank sedimentation than downstream variation (Walling and He, 1998;Middelkoop and Asselman, 1998;Thonon et al, 2007). Such trends were also observed at specific floodplain sections -site-scale -with uniform relief.…”
Section: Introductionmentioning
confidence: 99%
“…The results given in Table 6 indicate that the sedimentation rates range from less than 1 mm/a for the floodplains of the IJssel and Nederrijn-Lek rivers to about 15 mm/a for low lying parts of the Waal floodplain. (Middelkoop & Asselman, 1998;Middelkoop & Van der Perk, 1998) may cause that correlations between metal pollution of a soil versus factors such as distance to the main channel, local elevation or flooding frequency are low when larger areas are considered. Because of the reduction in pollution over the past decades, inventories of the metal pollution of the floodplains of the Rhine should not be based on shallow samples (see Hoogerwerf, 1992).This can be well illustrated when the total (excess) Zn content, M, in each soil profile is plotted against the average Zn concentration in the upper 10 cm of the profile, C 18 (Fig.…”
Section: Estimation Of Sedimentation Ratesmentioning
confidence: 99%